Long-term development of vegetation in established permanent field margins - Waldén, Emelie (SLU/Dept. of Ecology, 2011)
Biodiversity loss, pesticide drift and nutrient leakage are some of the negative effects caused by intensified agriculture. One measure to reduce these negative effects is to establish permanent field margins. Between 1988 and 1990 experiments with broadened permanent field margins were established at three sites near Flen and Uppsala in south of Sweden. One of the aims was to study how different treatments affected the margin vegetation and if the abundance of weeds could be suppressed. The treatments consisted of establishing new or broadening pre-existent field margins, sowing different seed-mixtures (e.g. “meadow plants”) and manage them by yearly mowing with removal of cut material. The vegetation was investigated at three occasions after establishment during a 20-year period. At the second and third occasion, adjacent untreated field margins were examined for comparisons.